Thanking Acts among The EFL Students at SMA Negeri 3 Singaraja - ., PUTU NARITA SARI; ., Prof. Dr. Dewa Komang Tantra, M.Sc.; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Universitas Pendidikan Ganesha, 2017)
Thanking acts are always used by the students at school. They are used for showing respect, building relationship and acknowledging the favor. However, the students do not know and understand about the appropriate sentence styles (forms) and the strategies of thanking acts. This study aimed at describing locutionary thanking acts, perlocutionary thanking acts, and strategies of thanking acts. The problems were focused on the locutionary acts (the verbal literal meanings of what are said) and perlocutionary acts (the responses to what are said). The research used a descriptive qualitative design. The subjects were EFL senior high school students from language and culture department. The data were collected through observing simulated role play speech encounters. The data were analyzed descriptively following the steps of identifying locutionary acts and perlocutionary acts, classifying them and drawing the conclusion. The results showed that most of the students employed informal forms as their locutionary thanking acts and formal-informal forms as their perlocutionary thanking acts. Also, the students mostly used explicit-emotional thanking as the strategy of their locutionary thanking acts and acceptance strategy as the perlocutionary thanking acts. This research was limited to the use of a role play under five situations.keyword : EFL students, speech acts, thanking acts forms, thanking acts strategies.